Impact of visual acuity on developing literacy at age 4–5 years: a cohort-nested cross-sectional study. Issue 2 (16th February 2016) - Bruce, Alison; Fairley, Lesley; Chambers, Bette; Wright, John; Sheldon, Trevor A
Abstract : Objectives: To estimate the prevalence of poor vision in children aged 4–5 years and determine the impact of visual acuity on literacy. Design: Cross-sectional study linking clinical, epidemiological and education data. Setting: Schools located in the city of Bradford, UK. Participants: Prevalence was determined for 11 186 children participating in the Bradford school vision screening programme. Data linkage was undertaken for 5836 Born in Bradford (BiB) birth cohort study children participating both in the Bradford vision screening programme and the BiB Starting Schools Programme. 2025 children had complete data and were included in the multivariable analyses. Main outcome measures: Visual acuity was measured using a logMAR Crowded Test (higher scores=poorer visual acuity). Literacy measured by Woodcock Reading Mastery Tests-Revised (WRMT-R) subtest: letter identification (standardised). Results: The mean (SD) presenting visual acuity was 0.14 (0.09) logMAR (range 0.0–1.0). 9% of children had a presenting visual acuity worse than 0.2logMAR (failed vision screening), 4% worse than 0.3logMAR (poor visual acuity) and 2% worse than 0.4logMAR (visually impaired). Unadjusted analysis showed that the literacy score was associated with presenting visual acuity, reducing by 2.4 points for every 1 line (0.10logMAR) reduction in vision (95% CI −3.0 to −1.9). The association of presenting visual acuity with the literacy score remained significant after adjustment for demographic and socioeconomic factors reducing by 1.7 points (95% CI −2.2 to −1.1) for every 1 line reduction in vision. Conclusions: Prevalence of decreased visual acuity was high compared with other population-based studies. Decreased visual acuity at school entry is associated with reduced literacy. This may have important implications for the children's future educational, health and social outcomes.